Examining the Thullatun (A Numerous Company) from among the First and A few from among the Latter Verses - mahdi motia; Mohsen Khaleghi; Peyman Kamalvand (آموزه‌های قرآنی)
God says the most of the forerunners are from among the First and a few of them are among from the Latter in the Waqiah (the inevitable) chapter, after He divides men in to three parts: The companions of the Right, the companions of the Left and the Foremost (in the faith). The interpretations of these verses have implied the objects of these concepts and determined the First and the Latter with the time criteria which the necessity of these sayings has been the decline in the forerunners in the time passing. According to the Quranic and traditional teachings, the First who flower their abilities and capacities in the light of God and monotheism, therefore they (the First) compose majority of the Foremost and the companions of the Right but the Latter who compose the minority of the Foremost while their spirit and abilities are not as the Firsts but it is not impossible to achieve the position of the Forerunners through the salvation. In this article, stating these terms in the Quranic and traditional teachings objectively has been explored in order to be acquainted with the spirit of the forerunners.